Therapeutic Efficacy of Chicken Egg Yolk Immunoglobulins Against Mycoplasma gallisepticum Infection in Chickens - Elsheikha, H.M.; Abbas, A.T.; Aziz, M.M. Abdel; Elshabiny, L.M. (International Journal of Poultry Science, 2008)
The focus of this report was to assess the role of passive immunization using immunoglobulins derived from chicken egg yolk in protection against M. gallisepticum infection in chickens. Immunoglobulins were produced by egg yolk technology. ELISA was used to evaluate their immunoreactivity and western immunoblotting demonstrated that chicken egg yolk immunoglobulins Y (IgY) were capable of recognizing M. gallisepticum immunoreactive antigens. Administration of IgY to experimentally infected broiler chickens afforded up to 70% protection rate as confirmed by culture analyses. Challenge of IgY - treated birds with M. gallisepticum virulent strain S6 revealed significantly (P< 0.05) lower isolation prevalence in comparison to control chickens treated with IgY from mock-immunized (control) hens that received the same bacterial challenge. Additionally, M. gallisepticum culture analysis from respiratory organs demonstrated that these antibodies protected chickens in a dose-dependent pattern against M. gallisepticum infection (i.e., increasing IgY titer resulted in decreased isolation rate). These findings demonstrate that IgY obtained from hens immunized by M. gallisepticum could provide an alternative approach for treatment of M. gallisepticum infection in chickens.